Medidas de núcleo de inflação no Brasil e a tendência de longo prazo nos preços: uma abordagem sobre decomposição de séries de tempo - Korek, Karoline Kwiatkowsk (2016)
The purpose of this study is to verify if the measures of core inflation calculated by Brazil ́s Central Bank are able to capture the trend in prices when there are movements and are therefore, good indicators for driving the monetary policy inserted in the context of the Target Inflation System. The approach of this study is to apply the Unrestricted Multivariate Unobserved Components Model on core inflation and headline inflation in order to estimate the permanent and transitory components, capturing the innovations using the prediction error decomposition. The aim of this study is to capture the magnitude of the trend and transitory disturbances of the core inflation and headline inflation and thus, identifying if the variables are good long-term indicators when there are movements in the prices.